The first isolation of Aspergillus allahabadii from a cormorant with pulmonary aspergillosis - Lim, Sue Yee; Kano, Rui; Ooya, Kenji; Kimura, Shunta; Yanai, Tokuma; Hasegawa, Atsuhiko; Kamata, Hiroshi (Shunkosha, 2016)
In this study, we report the first isolation of Aspergillus allahabadii from a Japanese cormorant with pulmonary aspergillosis. We performed molecular identification and antifungal susceptibility testing with the E-test. A 7-month-old male cormorant died because of uric acid deposition secondary to dehydration. Whitish nodular lesions were present on the caudal thoracic air sac in the right thoracic cavity. Histopathology revealed multifocal pyogranulomatous necrotic lesions with numerous fungal hyphae in the thoracic air sac. Identification of the etiologic agent was confirmed by comparative analyses of the sequences of the internal transcribed spacer (ITS) region and β-tubulin-encoding genes. According to the E-test, the minimum inhibitory concentrations of the isolate to amphotericin B, fluconazole, itraconazole, and voriconazole were 0.75 μg/ml, >256 μg/ml, 0.38 μg/ml, and 0.38 μg/ml, respectively.